CFD-based and experimental hydrodynamic characterization of the single-use bioreactor XcellerexTM XDR-10 - Kreitmayer, Diana; Gopireddy, Srikanth R.; Matsuura, Tomomi; Aki, Yuichi; Katayama, Yuta; Nakano, Takuya; Eguchi, Takuma; Kakihara, Hirofumi; Nonaka, Koichi; Profitlich, Thomas; Urbanetz, Nora Anne; Gutheil, Eva (Bioengineering, 2022)
Understanding the hydrodynamic conditions in bioreactors is of utmost importance for the selection of operating conditions during cell culture process development. In the present study, the two-phase flow in the lab-scale single-use bioreactor XcellerexTM XDR-10 is characterized for working volumes from 4.5 L to 10 L, impeller speeds from 40 rpm to 360 rpm, and sparging with two different microporous spargers at rates from 0.02 L min−1 to 0.5 L min−1. The numerical simulations are performed with the one-way coupled Euler-Lagrange and the Euler-Euler models. The results of the agitated liquid height, the mixing time, and the volumetric oxygen mass transfer coefficient are compared to experiments. For the unbaffled XDR-10, strong surface vortex formation is found for the maximum impeller speed. To support the selection of suitable impeller speeds for cell cultivation, the surface vortex formation, the average turbulence energy dissipation rate, the hydrodynamic stress, and the mixing time are analyzed and discussed. Surface vortex formation is observed for the maximum impeller speed. Mixing times are below 30 s across all conditions, and volumetric oxygen mass transfer coefficients of up to 22.1 h−1 are found. The XDR-10 provides hydrodynamic conditions which are well suited for the cultivation of animal cells, despite the unusual design of a single bottom-mounted impeller and an unbaffled cultivation bioreactor.
Im Titel ist das "TM" hochgestellt und als Trademarkzeichen dargestellt
Gesehen am 31.03.2022